ASSOCIATION OF MARITAL STATUS, EARLY MARRIAGE AND PARITY WITH FIBROADENOMA - Muhammad Saeed Akhtar (Army Medical College Rawalpindi, 2021)
Objective: To evaluate the association of marital status, early marriage and parity with fibroadenoma patients at a tertiary care hospital of Pakistan.